Health Counseling and COVID-19 Screening Test at Universitas Nasional in 2021: Penyuluhan Kesehatan Pemeriksaan COVID-19 di Universitas Nasional Tahun 2021 - Novelia, Shinta; Tiara Carolin, Bunga (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
Rapid tests for initial screening of COVID-19 are urgently needed given the very fast spread of the disease. However, WHO emphasized that this examination does not establish a clinical diagnosis of COVID-19 and is not recommended for triaging patients with suspected COVID-19, the rapid test is only an initial screening; Real-Time Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) must still confirm the results. Meanwhile, triage of patients uses a rapid risk assessment from the Ministry of Health which refers to the WHO Rapid Risk Assessment of Acute Public Health guidelines. In order to assist the government's program in preventing the spread of Covid-19, it is necessary to carry out health education about the behavior of preventing Covid-19 and early detection of Covid-19 by testing rapid antibodies at the National University. The results of the dedication activity showed that the participants were enthusiastic about listening to the material provided and participating in the inspection activities. Participants admitted that this inspection activity provided great benefits for breaking the chain of the spread of the coronavirus in the National University environment.